Harvest Pressure and Environmental Carrying Capacity: An Ordinal-Scale Model of Effects on Ungulate Prey. Issue 2 (20th April 2008) - Wolverton, Steve
Abstract : Zooarchaeologists have long realized the analytical potential of ungulate mortality data in studies of temporally shifting foraging efficiency. An additional but seldom examined form of evidence from ungulate remains is the morphometry of age-independent body size. Together simple bivariate morphometric and mortality data from ungulate remains reveal shifts through time in harvest pressure and/or environmental carrying capacity. A proposed model of these effects is validated using wildlife biology data from white-tailed deer (Odocoileus virginianus), an ungulate taxon that is very common in North American archaeological faunas. Several archaeological implications that bear on studies of foraging efficiency in subsistence hunting economies arise from this ordinal-scale model, such as the conditions under which harvest pressure increases or decreases or when carrying capacity rises or declines.